Hi sorry to bother you again, but I used the other one as an example and did #2. Can you check it?
r - m/x = e^2
-m/x = e^2 - r
m/x = r - e^2
m = x(r - e^2)
m/r - e^2 = x
And also I have two questions. Why did you multiply both sides by -1, and what is the purpose of swapping th order on the LHS? Thanks so much!
You wrote m/r- e^2= x and Pickslides wrote "be careful, though, use brackets m/(r- e^2)= x".
Which makes me ask- is your original problem r- m/x= e^2 (which is ) or (r- m)/x= e^2 (which is )? Those are very different equations with very different solutions.
Similarly, was your first problem h= d- b/x ( ) or h= (d- b)/x ( ?
pickslides assumed it was the first in both of those.